A Six Week Therapeutic Ballet Intervention Improved Gait and Inhibitory Control in Children With Cerebral Palsy—A Pilot Study - Lakes, Kimberley D.; Sharp, Kelli; Grant-Beuttler, Marybeth; Neville, Ross; Haddad, Fadia; Sunico, Rachel; Ho, Daniel; Schneider, Melinda; Sawitz, Sofia; Paulsen, Janine; Caputo, Kim; Lu, Kim D.; et al. (Frontiers in Public Health, 2019)
Children with cerebral palsy (CP) have motor impairments that make it challenging for them to participate in standard physical activity (PA) interventions. There is a need to evaluate adapted PA interventions for this population. Dance can promote coordination, posture, muscle strength, motor learning, and executive functioning. This pilot study evaluated the feasibility and the effects of a new therapeutic ballet intervention specifically designed for children with CP. Methods: Eight children with CP (9–14 y/o; 75% female) participated in a 6-week therapeutic ballet intervention. Outcomes were measured in multiple domains, including body composition (DXA), muscle strength (hand-grip dynamometer), habitual physical activity, gait and selective motor control functions, and executive functioning. Follow-up assessments of habitual physical activity, gait, and executive functioning were completed 4 to 5 weeks post-intervention. Results: Five of the eight participants were overfat or obese based on DXA percentage of body fat. All participants were below the 50th percentile for their age and gender for bone density. Four participants showed a trend to improve hand-grip strength in one hand only, while one improved in both hands. There were significant improvements in gait across time points (pre, post, and follow-up), specifically in time of ambulation (Xpre = 4.36, Xpost = 4.22, Xfollow−up = 3.72, d = 0.056, p = 0.02), and in step length (cm) on the right: Xpre = 48.29, Xpost = 50.77, Xfollow−up = 52.11, d = 0.22, p = 0.027, and left stride: Xpre = 96.29, Xpost = 102.20, Xfollow−up = 104.20, d = 0.30, p = 0.027, indicating gait changes in bilateral lower extremities. There was improvement in inhibitory control (d = 0.78; 95% Confidence Limit = ±0.71, p < 0.05) with large individual responses primarily among those above the mean at baseline. Conclusions: Therapeutic ballet may prove to be a useful intervention to promote physiological and cognitive functions in children with CP. Results demonstrated feasibility of the physical, physiological, and cognitive assessments and suggested improvements in participants' gait and inhibitory control with large individual responses. Modifications to personalize the intervention may be needed to optimize positive outcomes. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT03681171